استخدام مواقع التواصل الاجتماعي وعلاقته بتشتت الانتباه لدى تلاميذ سنة الثالثة ثانوي - بريبش, رونق; أوبيرة, كوثر (University of Eloued جامعة الوادي, 2023)
ملخص الدراسة: هدفت الدراسة الحالية إلى الكشف عن العلاقة بين استخدام مواقع التواصل الاجتماعي وتشتت الانتباه لدى تلاميذ ثالثة ثانوي. ولقد تم الاعتماد في هذه الدراسة على المنهج الوصفي الارتباطي لكونه مناسب لهذه الدراسة. تم إجراء الدراسة على عينة غرضية تكونت من " 50 " تلميذا يتمدرس بثانوية صنديد محمد منيب بلدية كونين, وسعد شعباني بلدية الرقيبة بولاية الوادي للموسم الدراسي:2022/2023 أما أدوات الدراسة فكانت مقياس تشتت الانتباه ومقياس مواقع التواصل الاجتماعي. وبعد إجراء المعالجة الإحصائية تم التوصل إلى النتائج التالية: - توجد علاقة ارتباطيه عكسية داله إحصائيا بين مواقع التواصل الاجتماعي و بُعد الأنشطة التعليمية لدى تلاميذ ثالثة ثانوي. . - توجد علاقة ارتباطيه عكسية دالة إحصائيا بين مواقع التواصل الاجتماعي وبُعد المهارات العقلية المرتبطة بتشتت الانتباه لدى تلاميذ ثالثة ثانوي. - لا توجد علاقة إرتباطية داله إحصائيا بين مواقع التواصل الاجتماعي وبُعد المهارات التفاعلية المرتبطة بتشتت الانتباه لدى تلاميذ ثالثة ثانوي. وبناء عليه تم التحقق من الفرضية العامة القائمة على وجود علاقة إرتباطية عكسية بين مواقع التواصل الاجتماعي وتشتت الانتباه لدى تلاميذ ثالثة ثانوي. Abstract: The present study aimed to reveal the relationship between the use of social networking sites and distracting attention. third secondary students. In this study, the descriptive correlative approach was relied upon because it is suitable for this study. The study was conducted on a purposive sample consisting of "50" students studying at the secondary school of Sandid Mohamed Mounib, municipality of Konin, and Saad Chaabani, municipality of Ragiba, in El Oued state, for the academic season: 2022/2023.. After statistical treatment there was a significant inverse association between distracting attention and Social networking sites scale. After performing the statistical treatment, the following results were obtained:  There is a statistically significant inverse correlation between social networking sites and the dimension of educational activities for third year secondary students.  There is a statistically significant inverse correlation between social networking sites and the dimension of mental skills related to distracting attention. third secondary students. - There is no statistically significant correlation between social networking sites and the dimension of interactive skills related to distracting attention third secondary students. - Accordingly, the general hypothesis based on the existence of an inverse correlation between social networking sites and distracting attention. third secondary students was verified.
دراسة ميدانية بثانوية صنديد محمد منيب وسعد شعباني ولاية الوادي
مذكرة ماستر في علوم التربية تخصص ارشاد وتوجيه
Keywords: مواقع التواصل الاجتماعي، Sites de réseautage social, social media sites; تشتت الإنتباه، Manque d'attention, Attention Deficit